Assessing coupling between soil temperature and potential air temperature using PALM-4U: implications for idealized scenarios - P. Glocke; C. C. Holst; B. Khan; B. Khan; S. A. Benz (Earth System Dynamics)
Underground heat extremes, amplified by factors such as underground infrastructure or poorly adjusted geothermal systems, have long been discussed in the geosciences. However, there is little emphasis on the exchange between these subsurface heat extremes and the atmosphere. To address the issue, this study investigates the impact of varying soil temperatures on potential air temperatures in an idealized domain using the turbulence- and building-resolving large-eddy-simulation urban microclimate model PALM-4U (Parallelized Large-Eddy Simulation Model for Urban Applications). This involves two steps. First, we test if and how idealized domains can be simulated, and second, the coupling between surface and subsurface energy fluxes, or rather temperatures in air and soil, is in focus. We develop several scenarios, distinguishing between cyclic and Dirichlet/radiation boundary conditions along the x axis, between summer and winter, and between various land cover types. Our results demonstrate that cyclic boundary conditions induce modifications in potential air temperatures due to changes in soil temperature. The magnitude of the impact varies with respect to the tested land covers, which primarily affect absolute temperatures. The time of day and season have a larger influence on the magnitude of the modifications. A 5 K increase in subsurface temperatures at 2 m depth results in a maximum increase of 0.38 K in near-surface potential air temperatures during winter between 09:00 and 10:00 local time after 3 d of simulation. When soil temperatures are decreased, we find predominantly inverse patterns. The least influence is found during summer at 09:00, when elevated soil temperatures increase potential air temperatures by only 0.02 K over short and tall grass and by 0.18 K over bare soil. When using Dirichlet/radiation boundary conditions, the atmosphere cannot develop freely, and changing soil temperatures do not impact potential air temperatures.